Graphite superlubricity enabled by triboinduced nanocontacts. (30th October 2021) - Buzio, Renato; Gerbi, Andrea; Bernini, Cristina; Repetto, Luca; Vanossi, Andrea
Abstract: Colloidal probe Atomic Force Microscopy allows to explore sliding states of vanishing friction, i.e. superlubricity, in mesoscopic graphite contacts. Superlubricity is known to appear upon formation of a triboinduced transfer layer, originated by material transfer of graphene flakes from the graphitic substrate to the colloidal probe. Previous studies suggest that friction vanishes due to crystalline incommensurability at the newly formed interface. However this picture still lacks several details, such as the roles of the tribolayer roughness and of loading conditions. Hereafter we gain deeper insight into the tribological response of micrometric silica beads sliding on graphite under ambient conditions. We show that the tribotransferred flakes behave as lubricious nanoasperities with a twofold role. First, they decrease the silica-graphite true contact area, in fact causing a breakdown of adhesion and friction by one order of magnitude. Second, they govern mechanical dissipation through the specific energy landscape experienced by the topographically-highest triboinduced nanoasperity. Remarkably, such contact junctions can undergo a load-driven atomic-scale transition from continuous superlubric sliding to dissipative stick-slip, that agrees with the single-asperity Prandtl-Tomlinson model. Superlubricity in mesoscopic silica-graphite junctions may therefore arise from the load-controlled competition between interfacial crystalline incommensurability and contact pinning effects at one dominant nanoasperity. Graphical abstract: Image 1 Highlights: Graphene nanoflakes are tribotransferred at the silica-graphite interface. Triboinduced interfacial roughness controls adhesion and friction forces. Contact asperities show a load-controlled regime of superlubric sliding. Atomic-scale dissipation agrees with the Prandtl-Tomlinson model. Friction reflects the energy landscape of the highest triboinduced nanoasperity.